To study the expression of estrogen, progesterone receptor and p53 immunohistochemistry markers in subtyping endometrial carcinoma - Anuja Yadav; Anuradha Sistla; Swarnalata Gowrishankar; Michelle de Padua; Tejal Modi; Rallabandi Himabindu; Neha Agarwal; Aditya Kulkarni; Trilok Bhandari; Hemanth Vudayaraju; Chinnababu; Vijay A Reddy (Wolters Kluwer Medknow Publications, 2024)
Background: Endometrial cancer is one of the most commonly diagnosed cancers in women worldwide. Aim and Objectives: To study the expression of estrogen receptor (ER), progesterone receptor (PR) and p53 immunohistochemistry (IHC) markers in subtyping endometrial carcinoma. Materials and Methods: A total of 100 cases of carcinoma endometrium submitted during January 2016 to October 2018 were included in our study. The ER, PR and p53 expressions were scored as per the adopted scoring system. Agreement between ER, PR and p53 IHC expression and the consensus HE diagnosis, FIGO grading and tumour staging were assessed using Chi square tests. Results: There was a statistical association between ER, PR and p53 status and tumour histologic type with a P value < 0.01. There was no statistical significance observed between ER and PR expressions and different FIGO grades. Statistical significance (P = 0.036) between p53 and different FIGO grades seen. No statistical significance was observed between ER, PR and p53 expressions and different tumour stages and tumour invasiveness. There was a statistical association between ER and PR status and lymph node metastasis. p53 did not show a statistical significance. Conclusion: Combination of ER, PR and p53 IHC markers can be used to distinguish type 1 and type 2 endometrial cancers. PR expression is more specific than ER in endometrioid carcinomas. p53 expression is more specific in serous carcinoma, however, p53 IHC alone cannot be used to distinguish different grades of endometrioid carcinomas as there is variability of staining in endometrioid carcinomas.